Ambiguities from Nuclear Interactions in the \(^{12}\)C(p,2p)\(^{11}\)B Reaction - Nguyen, Tri Toan Phuc; Ogata, Kazuyuki; Nguyen, Hoang Phuc; Bui, Duy Linh; Vo, Hong Hai; Le, Xuan Chung (Communications in Physics, 2022)
We investigate the impact of ambiguities coming from the choice of optical potentials and nucleon-nucleon scattering cross sections on the spectroscopic factors extracted from the 12C(p,2p)11B reaction. These ambiguities are evaluated by analyzing the cross sections of the 12C(p,2p)11B reaction at 100 and 200 MeV within the framework of the distorted-wave impulse approximation with realistic choices of nuclear inputs. The results show that the studied ambiguities are considerably large in this energy region and careful choices of nuclear inputs used in the reaction calculations are required to extract reliable structure information.